INFLUENCE OF THE DIGITAL ECONOMY ON THE COUNTRY’S DEVELOPMENT - Xodjibaeva Ikbola Valiyevna; Karimov Abdurahim Muzaffar ogli (Web of Journals Publishing, 2024)
The article explores the possibilities of the digital economy, as well as the gradual transition to the digital economy of Uzbekistan in the context of globalization and technological development of the world economy. The influence of the digital economy in the development of the country’s economy, social sphere and public administration.
Keywords: Digital economy, investment climate, automation, digital technology, social sphere, technological base, digital infrastructure, business environment, private sector, institutional environment.